Submersible solar powered pump system design for sustainable agriculture using: https://doi.org/10.69692/SUJMRD0802244 - SIPHAXAY, Khamphoungeun; SISOMPHOU, Somphan; SENGPARERT , Boutthamaly; SOULISOMBOUN, Dee (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
Current climate change has many implications for people's livelihoods, one of which is the lack of seasonal rainfall, leading to drought, which in turn reduces agricultural yields. Therefore, people have to plant dry season crops, and in the dry season, crops have to rely on water from rivers and streams. But some areas where there is no stagnant water or stagnant water are very dry. So, our team did experimental research and studied the feasibility of using solar groundwater pumping systems in agriculture. It will cover the design, control, and know the strengths and weaknesses of the system, and its suitability to be used in our country, especially in the eight Northern provinces. In this research, we designed and used a Submersible solar-powered pump system, after installation, the system will work automatically without the need to turn it on and off. The panel size used is 330 watts, two panels serial connection for a total of 660 watts; the Submersible solar-powered pump is 400 watts, 48 voltages, Automatic control system, Groundwater depth 68 meters, the diameter of the surface pipe 0.1 meters, The diameter of the suction pipe has a cross-sectional area of 0.025 meters. Experimentation shows the water pump deep at 30 m can absorb more water than 25 m deep. The capacity of the system to be used for agriculture in one day can use 6.13 m3 of water, which is enough for cultivation in an area of 8,000 m2 or more, depending on the type of crop grown. The power generated per day is 3,142 W and is used at 3.14 kWh per day as well or 94.24kWh per month which is sufficient for the use of the system. In cash compared to the electricity consumption from the Electricity du Laos is 39,000 LAK per month. The maximum amount of water collected is 6.13 m3 per day or 184 m3 per month, which is 646,644 LAK per month compared to the water supply system, in the analysis of the cost of installation is 31 months or 2 years and 7 months.